Analisis Produktivitas Gen-Z Divisi Pemasaran Properti di Makassar Dengan Sistem WFA - Akhmad Ariesta Gemilang; Fahrul Riza (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The transformation of the world of work due to digitalization and the COVID-19 pandemic has encouraged the implementation of flexible work systems, one of which is Work From Anywhere (WFA). This change is in line with the entry of Generation Z (Gen Z) as the dominant group in the world of work which has the characteristics of being adaptive to technology and prioritizing flexibility. The property sector in Makassar City, especially the marketing division, which previously applied conventional work patterns, is an important context for studying Gen Z's work productivity in the WFA system. This research aims to analyze the influence of work motivation, work commitment, work-life balance, organizational culture, WFA system, psychological well-being, and work flexibility on Gen Z work productivity in the marketing division of property companies in Makassar City. This research uses a quantitative approach with a survey design. The research population was all 100 Gen Z employees in the marketing division of property companies in Makassar City, all of whom were sampled using a total sampling technique. Data was collected through questionnaires as primary data and analyzed using linear regression analysis with the help of SPSS software. The research results show that work motivation, the WFA system, and psychological well-being have a positive and significant effect on Gen Z's work productivity. Meanwhile, work-life balance and work flexibility have a significant effect in a negative direction. Work commitment and organizational culture do not have a significant effect on work productivity. The conclusion of this research confirms that increasing Gen Z's work productivity in the WFA system is strongly influenced by motivational factors and psychological well-being as well as effective management of work flexibility.